2013
DOI: 10.1088/0953-8984/26/1/016001
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic investigation by heat capacity measurements of ferrimagnetic A2Mn[Mn(CN)6] (A=K, Rb, Cs) Prussian blue compounds

Abstract: Heat capacity measurements of a new series of Prussian blue analogs of A2Mn[Mn(CN)6] (A=K, Rb, Cs) composition were performed using thermal relaxation calorimetry. The Cs compound has a face-centered cubic structure with a linear Mn-C≡N-Mn linkage, while the monoclinic Rb and K compounds have nonlinear Mn-C≡N-Mn linkages. For all of the compounds, large broad thermal anomalies associated with magnetic transitions were observed in the temperature dependence of the heat capacity. The systematic changes in the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This broadening is reflected in the peak width of the FC curves. The upward shift of the transition temperature is consistent with the behavior produced by the chemical pressure 13,18 because the external pressure contracts the interstitial space in the crystal and bends the MnNC angle. The monotonous change of T c with pressure demonstrates that the external pressure plays a role similar to that of the chemical pressure effects arising from different sized cations in this compound (Table 1).…”
Section: ■ Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This broadening is reflected in the peak width of the FC curves. The upward shift of the transition temperature is consistent with the behavior produced by the chemical pressure 13,18 because the external pressure contracts the interstitial space in the crystal and bends the MnNC angle. The monotonous change of T c with pressure demonstrates that the external pressure plays a role similar to that of the chemical pressure effects arising from different sized cations in this compound (Table 1).…”
Section: ■ Discussionsupporting
confidence: 72%
“…The thermodynamic work recently reported by Kawamoto et al revealed that the magnetic transitions occur as a 3D bulk ordering of high-spin Mn II ( S = 5 / 2 ) and low-spin Mn II ( S = 1 / 2 ) . The heat capacity peak under magnetic field shows an upward shift with an increase in the magnetic field, as is typically observed in 3D ferrimagnetic/ferromagnetic orderings.…”
Section: Introductionmentioning
confidence: 82%
“…Heat capacity, C p , studies reveal a peak in C p ( T , H ) that increases with an increasing magnetic field ( H ) in accord with ferrimagnetic ordering for A 2 Mn­[Mn­(CN) 6 ] (A = K, Rb, and Cs) . This also suggests that the magnetic and thermodynamic properties are strongly affected by lattice distortion such as the ∠Mn–N–C bending angle.…”
Section: Introductionmentioning
confidence: 89%
“…15 Heat capacity, C p , studies reveal a peak in C p (T,H) that increases with an increasing magnetic field (H) in accord with ferrimagnetic ordering for A 2 Mn[Mn(CN) 6 ] (A = K, Rb, and Cs). 16 This also suggests that the magnetic and thermodynamic properties are strongly affected by lattice distortion such as the ∠Mn−N−C bending angle. To further understand this system, the pressure effect on T c , T c (P), was studied for A 2 Mn[Mn(CN) 6 ] (A = K, Rb, and Cs) 17 and herein for A = Na.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the group of Miller, a series of alkali metal A 2 Mn 2+ Mn 2+ (CN) 6 compounds with A = Na, [165] K, [166] Rb, [166] and Cs [167] were investigated starting in 2010. It is linear and well known to bind multiple metals, such as Fe in prussian blue.…”
Section: Organic X-site: Hp(x)mentioning
confidence: 99%